2016
DOI: 10.22456/2316-2171.80792
|View full text |Cite
|
Sign up to set email alerts
|

Potenciais Evocados Auditivos De Longa Latência E Potencial Cognitivo Em Indivíduos Afásicos

Abstract: Objetivo: Analisar os achados do potencial evocado auditivo de longa latência (PEALL) e cognitivo (P3) em indivíduos afásicos. Método: Foram avaliados 17 indivíduos afásicos em decorrência de acidente vascular encefálico (AVE), com média de 63,4 anos, por meio dos PEALL e P3. Resultados: Dos 17 indivíduos, apenas 11 obtiveram as ondas P1 e N1, 10 apresentaram a onda P2 e apenas seis apresentaram as ondas N2 e P3. Foram encontradas associações quando correlacionados os achados do PEALL com gênero, idade, escola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 5 publications
0
2
1
2
Order By: Relevance
“…When researching the cognitive potentials, mean P3 latency values of 318.1 ms for the right ear and 331.9 ms for the left ear were observed in the SG with the toneburst stimulus (Table 3). These values are lower than those from another study 8 , which presented a mean P3 latency value of 369.7 ms, and yet another 9 , with mean P3 latency value of 383.1 ms. In this study, latency was higher for the left ear, which agrees with another study 23 , in which worse P3 latency and amplitude results were observed, always for the left ear, in aphasic individuals with left hemisphere injury caused by a stroke.…”
Section: Discussioncontrasting
confidence: 72%
“…When researching the cognitive potentials, mean P3 latency values of 318.1 ms for the right ear and 331.9 ms for the left ear were observed in the SG with the toneburst stimulus (Table 3). These values are lower than those from another study 8 , which presented a mean P3 latency value of 369.7 ms, and yet another 9 , with mean P3 latency value of 383.1 ms. In this study, latency was higher for the left ear, which agrees with another study 23 , in which worse P3 latency and amplitude results were observed, always for the left ear, in aphasic individuals with left hemisphere injury caused by a stroke.…”
Section: Discussioncontrasting
confidence: 72%
“…As for LLAEP, studies have shown that aphasics have greater P300 wave latency in the left ear of individuals with left hemisphere damage caused by a stroke. This suggests that absent or abnormal P300 responses may be related to linguistic changes, corroborating the sensory and cognitive difficulties in processing message decoding 29,30 .…”
Section: Cross-sectional Studymentioning
confidence: 54%
“…Concordantly, studies 22,[28][29][30] in aphasic populations demonstrated increased latency or absent waves. The increase in latencies was related to the difficulty that aphasic individuals tend to have in situations involving auditory discrimination, memory, and attention mechanisms.…”
Section: Cross-sectional Studymentioning
confidence: 60%
“…No exame PEALL, as pesquisas têm demonstrado que os afásicos apresentam latência da onda P300 maior para a orelha esquerda em indivíduos com lesão no hemisfério esquerdo causada pelo acidente vascular cerebral (AVC), o que sugere que a ausência ou alteração da resposta P300 pode estar relacionada à alteração linguística, corroborando as dificuldades no processamento de decodificação de mensagens a nível sensorial e cognitivo 29,30 .…”
Section: Revisão Da Literaturaunclassified
“…Em conformidade, estudos 22,[28][29][30] realizados com população afásica demonstraram latência aumentada ou ausência das ondas. O aumento das latências foi relacionado à dificuldade que indivíduos afásicos tendem a apresentar em situações que envolvem mecanismos de discriminação auditiva, memória e atenção.…”
Section: Revisão Da Literaturaunclassified